Red long lasting phosphorescence of Eu3+ doped BiOCl semiconducting polycrystals - 周玉婷 宋志国 李永进 刘群 徐祖元 胡锐 张相周 邱建备 杨正文 (Journal of rare earths, 2016)
The exploration of novel long lasting red phosphors is still of importance due to expected commercial applications and scientific interests. In this work, we reported the red long lasting phosphorescence（LLP） from Eu3+ doped BiOCl semiconductor polycrystals. The LLP property of the red phosphor is relatively weak due to less trap density, but the excitation band of LLP stems from the energy gap transition of semiconductor, offering experimental evidence for energy transfer between BiOCl semiconductor and Eu3+ ions. Although the afterglow duration of Eu3+ doped BiOCl was short temporarily, this work may open a novel kind of red LLP phosphors.